SENSOR SOIL MOISTURE UNTUK PENYIRAMAN TANAMAN DALAM MENGHADAPI VARIABILITAS CUACA - Khairunnisya, Aqilla; Khairunnisa’; Merinda, Siska (Teknik Elektro Polsri, 2024)
The instability of weather conditions marked by extreme temperature fluctuations and irregular rainfall patterns significantly impacts agriculture, causing issues of drought or excessive soil moisture. An automated system capable of continuously measuring soil moisture and providing precise plant irrigation is essential. However, energy efficiency remains a primary challenge. Innovations in automatic irrigation technology are crucial, focusing on developing systems efficient in soil moisture measurement and energy usage. Integrating advanced, energy-efficient sensors presents an intriguing solution to maintain precise performance while reducing power consumption. This research explores the design of soil moisture measurement tools, optimizing plant irrigation systems, and the functionalities of sensors. Sensor reliability is a primary concern due to its operation under diverse environmental conditions. The tool's development needs to consider energy efficiency limitations and its scalability with existing irrigation systems on a larger scale. The development of this tool aims to enhance agricultural responsiveness to weather changes by accurate soil moisture monitoring and automated irrigation. It seeks to improve crop quality while reducing water and energy wastage in agricultural management.